In vitro Effects of Aprosulate sodium, a Novel Anticoagulant, On Platelet Activation: Possible Mechanism for Antiplatelet Action - Sugidachi, Atsuhiro; Breiter, Norbert; Ogawa, Taketoshi; Asai, Fumitoshi; Koike, Hiroyuki (Thrombosis and Haemostasis, 1996)
Aprosulate sodium, a bis-lactobionic acid amide derivative, is a novel synthetic polyanion with potent anticoagulant activities. In the present study, the effects of aprosulate on platelet aggregation were investigated in a plasma-free system. Aprosulate inhibited thrombin (0.03-0.3 U/ml)-induced aggregation in rat washed platelets in a concentration-dependent manner, with an IC50 value of 0.38 Μg/ml. In contrast, aprosulate, at up to 10 Μg/ml, did not affect collagen (1 Μg/ml) - or ADP (3 ΜM)-induced aggregation. In fura 2-loaded platelets, aprosulate (1-10 Μg/ml) inhibited intracellular Ca2+ mobilization induced by thrombin, but not that by ADP. Protamine, a highly basic protein, abolished aprosulate-mediated inhibition of thrombin-induced platelet aggregation, suggesting that the observed inhibition is primarily due to the negative charge contained on the aprosulate molecule. In human platelets, aprosulate inhibited thrombin-induced aggregation, but failed to inhibit platelet aggregation induced by SFLLRN, a synthetic tethered ligand of a thrombin receptor. Antiplatelet profiles of aprosulate were largely similar to those of heparin, although heparin inhibited both thrombin- and collagen-induced aggregation. These in vitro studies indicate that aprosulate is capable of inhibiting thrombin-induced platelet activation and that this effect is independent of its anticoagulant activity. These results suggest that the polyanionic feature of aprosulate plays an essential role in promoting its antiplatelet activities, and that a plausible mechanism to explain the observed inhibition conferred by this agent, would be one which involves blocking the platelet-thrombin interaction.